Perceiving the other: experience report on the phenomenological interview (Research, Society and Development, 2020)
This work aims to report the experience of the phenomenological interview in the production of data from the doctoral thesis with adult and elderly patients with venous ulcers, supported by the Merleaupontian framework. This is a descriptive research, with a qualitative approach, an experience report type. The field of investigation was the Wound Repair Ambulatory of Hospital Universitário Antônio Pedro. Data collection took place from June to December 2016, using the phenomenological interview instrument. The report points out that the collection of data through the phenomenological interview allowed to experience significant experiences in view of the ontic and ontological dimensions of the participants. In view of the above, it is concluded that the phenomenological interview allows to go to the heart of people's lived experiences, allowing their narration in order to bring to the fore internalized consciousness, which allows the nakedness of each individual's “cogito”.